Effect of loading rate on mechanical properties of micro-sized oak wood - Büyüksarı, Ümit (Maderas. Ciencia y Tecnología, 2017)
The aim of this study was to investigate the effect of loading rate on the micro-mechanical properties of oak (Quercus petraea) wood. Bending strength, modulus of elasticity in bending, compression strength parallel to the grain and tensile strength parallel to the grain were determined using microsized test samples. Three different loading rates were used for each test. The first loading rates were determined according to related ISO standards and the second and third loading rates were determined for half and a quarter of the standard loading rates. Results showed that the loading rate significantly affected the modulus of elasticity, tensile strength and compression strength of the oak wood, while the bending strength was not affected.